About Fermat

25/11/2008 - 18:32 von Peter Heckert | Report spam
c^n = a^n + b^n
c^n * (a^n + b^n)^n = (a^n + b^n) * (a^n + b^n)^n

Please look also at www.hphsite.de

Thanks,

Peter
 

Lesen sie die antworten

#1 Gottfried Helms
25/11/2008 - 20:26 | Warnen spam
Am 25.11.2008 18:32 schrieb Peter Heckert:
c^n = a^n + b^n
c^n * (a^n + b^n)^n = (a^n + b^n) * (a^n + b^n)^n

Please look also at www.hphsite.de

Thanks,

Peter


Hallo Peter -

*tieeeef* durchaatmen ... nicht vergessen

<G>

Ähnliche fragen